Faktor-Faktor Yang Mempengaruhi Pertumbuhan Ekononomi Sektor Perikanan di Indonesia - Muhammad irfan; Sri Ulfa Sentosa; Rusy Dina (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to analyze the effects of fish consumption, number of fishermen, investment, and exports on the economic growth of the fisheries sector in Indonesia. The data used is panel data from 32 provinces over the 2018–2023 period. The analytical method employed is panel data regression using the Fixed Effect Model (FEM) approach. The results show that fish consumption, number of fishermen, and exports have a positive and significant effect on the growth of the fisheries sector. This indicates that increases in these variables contribute to the acceleration of fisheries GDP growth. On the other hand, investment shows a negative and insignificant effect, reflecting the suboptimal realization and impact of investments in this sector. These findings highlight the importance of strengthening domestic consumption, empowering fishermen, and increasing export activities as key strategies to support sustainable economic development in Indonesia’s fisheries sector.